2022
DOI: 10.21203/rs.3.rs-1773610/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A comparative study by using machine learning classifiers to enhance classification and prediction of heart failure disease

Abstract: PurposeHeart failure is a complex clinical condition when the heart cannot provide blood with enough flow for the body's needs. It is a major clinical and public health problem. Even if heart failure is not yet diagnosed, it is important to get your health checked every three to six months. This study aims to improve the accuracy of diagnosing heart failure by using machine learning classifiers such as Recursive Feature Elimination (RFE) and Synthetic Minority Oversampling Technique (SMOTE). MethodsHeart fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Traditional biostatistics analyses have also affirmed the importance of feature ranking carried out via machine learning [9]. Employing techniques such as Recursive Feature Elimination (RFE) with Random Forest and Logistic Regression has led to improved model performance [10]. Notably, studies have found that utilizing a subset of features yields better performance compared to using all available features [10].…”
Section: IIImentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional biostatistics analyses have also affirmed the importance of feature ranking carried out via machine learning [9]. Employing techniques such as Recursive Feature Elimination (RFE) with Random Forest and Logistic Regression has led to improved model performance [10]. Notably, studies have found that utilizing a subset of features yields better performance compared to using all available features [10].…”
Section: IIImentioning
confidence: 99%
“…Employing techniques such as Recursive Feature Elimination (RFE) with Random Forest and Logistic Regression has led to improved model performance [10]. Notably, studies have found that utilizing a subset of features yields better performance compared to using all available features [10]. The ROC curve visually illustrates the trade-off to between the true positive rate and the false positive rate for a binary classification model across different classification thresholds, aiding in model evaluation and comparison [11].…”
Section: IIImentioning
confidence: 99%